The Slavic hamlet round a cult green as the precursor of the regular rundling ot the medieval Frankish-German colonisation - Nitz, Hans-Jürgen (ERDKUNDE, 1998)
Two versions of a rural settlement type are discussed, which generally are taken together under the term Rundling because of the arrangement of the houses round a central green. But actually the two differ: the one form is more irregular and associated with block fields, the other regular with strip fields according to the feudal Hufen system. As is demonstrated, the irregular form originated from Slavic times while the regular form was created under feudal conditions in the medieval period. The author discusses the conditions under which in certain regions the Slavic hamlet round a green could persist, in which regions it was transformed into the regular Rundling and where and under which circumstances this transformation movement from above was initiated. Finally a historical source of the 17th century is quoted, which proves that the central green traditionally served the pagan cult of the Slavs.